The Alchemist and Medieval Faerie Romance. Issue 2 (November 2019) - Bull, Steve
Abstract : In The Alchemist, Doll's faerie queen is frequently interpreted by critics as representative of Jonson's scepticism toward folkloric belief and superstition. The supernatural-monarch-come-prostitute who appears before Dapper the clerk is thought to be drawn from contemporary accounts of cozeners who would claim to be in contact with the faerie realm in order to part gullible patrons from their money. Jonson's faerie queen thus fits into wider critical discussions on the nature of faeries in Early Modern drama, in which faeries are frequently defined as deriving from rural and domestic folkloric tradition. However, whilst there is certainly some truth to the significance of folklore in representations of faeries on the early modern stage (see Shakespeare's Puck in A Midsummer Night's Dream, for example), such arguments have a tendency to downplay the significance of romance in Early Modern society and the ongoing influence of medieval romance convention in the way that faeries are incorporated into Early Modern literature and drama. This essay focuses on The Alchemist as an example of the continued importance of romance in shaping the themes and motifs that are associated with Early Modern faeries. Doll's faerie queen appears as part of a con enacted by the three cozeners, but her role and appearance still draw on certain romance motifs that equate faeries with wealth, aristocracy, and the testing of human morality. Through recognising a connection to romance in Jonson's work, this essay questions how we might better appreciate the meaning of The Alchemist 's faerie queen episodes. Jonson, without relinquishing his sceptical approach to the supernatural, uses these motifs as a way of exploring themes of greed, social mobility, and new wealth, themes that permeate throughout the play and throughout his work as a whole.